Low Carbon Development Workshop, New Delhi India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Many governments in South Asia have focused their agricultural policies on increasing agricultural production to meed food security, with few of them including mitigation into their agricultural sector. While opportunity exists for reducing Green House Gas (GHG) emissions from agriculture, the emissions are expected to increase with population growth and impact productivity. To turn this around adaptation and mitigation programs needs to be mainstreamed into agricultural plans, in order to get strong climate smart programs. This demands urgent policy decisions and targeted actions to balance agricultural production with GHG emissions. This was the backdrop for the low carbon development workshop.